Aspirin ameliorates lung cancer by targeting the miR‐98/WNT1 axis. Issue 4 (12th February 2019) - Gan, Huizhu; Lin, Lin; Hu, Nanjun; Yang, Yang; Gao, Yu; Pei, Yu; Chen, Kang; Sun, Butong
Abstract : Background: Aspirin, an anti‐inflammatory drug, has been widely investigated in the treatment of many cancer types, including colorectal, ovarian, breast, and prostate cancers. MicroRNAs (miRNAs) are the most well studied noncoding RNAs in cancers. In the current study, we were interested in defining the function of aspirin in lung cancer treatment and the related noncoding RNAs involved in this process. Methods: The function of aspirin in lung cancer growth was evaluated by cell viability and colony formation assays. Screening of miRNAs affected by aspirin was performed through quantitative real‐time PCR. Prediction of miR‐98 targeting WNT1 was performed using online bioinformatics software and was further confirmed by luciferase reporter gene analysis. The levels of miR‐98 and WNT1 were tested through immunoblotting and quantitative real‐time PCR analysis in lung cancer cells under aspirin treatment. Results: Cell viability was sharply suppressed in lung cancer cells with an increasing dose of aspirin. Aspirin markedly weakened the malignant colony formation ability of lung cancer cells. One out of six tumor suppressor miRNAs could be obviously regulated by aspirin in lung cancer cells. The inhibition of miR‐98 on the luciferase activities of wild‐type 3' untranslated region vectors of WNT1 was clearly revealed in lung cancer cells. Meanwhile, the inhibitor of miR‐98 increased the luciferase activities of wild‐type 3' untranslated region vectors of WNT1. After treatment with aspirin the expression of miR‐98 was induced and then its target gene, WNT1, was depressed in the cells. Conclusion: Aspirin targets the miR‐98/WNT1 axis to ameliorate lung cancer development.